Localization and Dynamics of Glucocorticoid Receptor at the Plasma Membrane of Activated Mast Cells. Issue 10 (25th February 2014) - Oppong, Emmanuel; Hedde, Per Niklas; Sekula‐Neuner, Sylwia; Yang, Linxiao; Brinkmann, Falko; Dörlich, René M.; Hirtz, Michael; Fuchs, Harald; Nienhaus, Gerd Ulrich; Cato, Andrew C. B.
<x xml:space="preserve">Abstract</x> In addition to their actions in the cell nucleus, glucocorticoids exhibit rapid non‐nuclear responses that are mechanistically not well understood. To explain these effects, the localization of a glucocorticoid receptor (GR) expressed in mast cells as a GFP fusion was analyzed after activation of the cells on allergenic lipid arrays. These arrays were produced on glass slides by dip‐pen nanolithography (DPN) and total internal reflection (TIRF) microscopy was used to visualize the GR. A rapid glucocorticoid‐independent and ‐dependent recruitment of the GR‐GFP to the plasma cell membrane was observed following contact of the cells with the allergenic array. In addition, the mobility of the GR at the membrane was monitored by fluorescence recovery after photobleaching (FRAP) and shown to follow binding kinetics demonstrating interactions of the receptor with membrane‐bound factors. Furthermore the recruitment of the GR to the cell membrane was shown to result in a glucocorticoid‐mediated increase in Erk phosphorylation. This is evidenced by findings that destruction of the membrane composition of the mast cells by cholesterol depletion impairs the membrane localization of the GR and subsequent glucocorticoid‐mediated enhancement of Erk phosphorylation. These results demonstrate a membrane localization and function of the GR in mast cell signaling.